2020
DOI: 10.3892/mmr.2020.11014
|View full text |Cite
|
Sign up to set email alerts
|

Advances of the experimental models of idiopathic membranous nephropathy (Review)

Abstract: idiopathic membranous nephropathy (iMn) is one of the main types of chronic kidney disease in adults and one of the most common causes of end-stage renal disease. in recent years, the morbidity of iMn among primary glomerular diseases has markedly increased, while the pathogenesis of the disease remains unclear. To address this, a number of experimental models, including Heymann nephritis, anti-thrombospondin type-1 domain-containing 7a antibody-induced iMn, cationic bovine serum albumin, anti-human podocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 111 publications
1
10
0
Order By: Relevance
“…Stage IV: according to the optical microscopy, the basement membrane thickened greatly. Electron microscopy showed that the deposit lost the electron density, and irregular electron translucent areas appeared in the irregularly thickened base film [13].…”
Section: Criteria For Pathological Staging Of Membranousmentioning
confidence: 99%
“…Stage IV: according to the optical microscopy, the basement membrane thickened greatly. Electron microscopy showed that the deposit lost the electron density, and irregular electron translucent areas appeared in the irregularly thickened base film [13].…”
Section: Criteria For Pathological Staging Of Membranousmentioning
confidence: 99%
“…The HN rat model is regarded as a classic animal model due to its high similarity in pathology to human IMN. But Heymann rats were created by injecting antibodies or antigens into the rats and could not simulate the process of an autoimmune response (Jiang et al, 2020), which hinders the study of herb on autoimmune response. Second, the complexity and diversity of the components of herb medicine.…”
Section: Difficulties In the Research Of Chinese Medicine In Imnmentioning
confidence: 99%
“…In addition, several latest publications have shown that MN was associated with the dysbiosis of gut microbiota and dysregulation of long non-coding RNAs ( Zhang et al, 2020b ; Dong et al, 2020 ; Luan et al, 2022 ; Jin et al, 2019 ). These advances were inspired by using animal models of IMN, including Heymann nephritis and cationic bovine serum albumin (CBSA)–induced MN ( Jiang et al, 2020 ). The model of Heymann nephritis put forward the concept that a podocyte antigen, namely, megalin, was a target of antibody-forming in situ immune complexes, whereas CBSA-induced MN first reflected the case of planted antigen ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other antigens including aldose reductase, superoxide dismutase-2, and α-enolase were also found in human, although their function remains to be established because they were not detected on normal podocyte surfaces ( Prunotto et al, 2010 ). In addition, endogenous podocyte antigens and exogenous antigens including CBSA were also involved in patients with early-childhood MN ( Ayalon and Beck, 2015 ; Jiang et al, 2020 ). Taken together, these studies exhibited a new era for the diagnosis, monitoring, and prognosis of MN from early infancy to adulthood.…”
Section: Introductionmentioning
confidence: 99%